Ritual Kaghoghoniwi Terhadap Orang Yang Telah Meninggal Pada Masyarakat Muna Di Desa Bangkali - WaOde Natasya Pratiwi; La Niampe; Komang Wahyu Rustiani (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
The kaghoghoniwi ritual is a ritual performed by the Muna people in Bangkali Village during ceremonies of death and other celebrations. This ritual is not well known by the Bangkali village community, especially the milineal generation that can cause this ritual to become extinct, so researchers are interested in conducting research with the title "Speech in the Kaghoghoniwi Ritual Against People Who Have Died in Muna Communities in Bangkali Village". The purpose of this study was to determine the implementation process and understand the meaning contained in the kaghoghoniwi ritual utterances in the Muna community in Bangkali Village. The method used in this study is qualitative research. Data collection is done by observation techniques, in-depth interviews, and documentation. The technique of determining informants in this study was a combination of purposive sampling and snowball. Data analysis techniques consisted of data collection, data reduction, data presentation, and drawing conclusions. The results showed the process of implementing the kaghoghoniwi ritual and the utterances spoken when summoning ancestral spirits had changed, where the kaghoghoniwi ritual process carried out by the Bangkali village community was now combined with the haroa tradition. The meaning of the utterance expressed in the implementation of the kaghoghoniwi ritual used to be meaningful to summon the spirits of ancestors or families who had died to eat, while the present speech means that the prayers that we pray to the deceased / deceased can be delivered.Keywords: Kaghoghoniwi Ritual, Meaning, speech.